2013
DOI: 10.1155/2013/738014
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastoma of the Female Breast with Admixed but Distinct Foci of Spindle Cell Lipoma: A Case Report

Abstract: Mammary myofibroblastoma (MFB) is a rare benign spindle neoplasm that affects both sexes with a male predominance. It can exhibit a wide range of histological patterns. We report a case of epithelioid/spindle MFB of the female breast with admixed, but distinct, foci of spindle cell lipoma. Whilst all the spindle cells within the tumour expressed CD34, AR, ER, BCL2, and CD10, only those within the myofibroblastoma expressed desmin and only those within the lipomatous areas expressed S100. This finding, to our k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…Hence, the immunohistochemical coexpression of CD34, actin and calponin in our case would favor the existence of a link between NMB and myofibroblastoma. On the other hand, it is widely accepted that myofibroblastoma and spindle cell lipoma share many features [ 10 ], including genetic aberrations [ 11 ], and it is well known that their morphologic findings may occasionally overlap [ 12 ]. Thus, it seems reasonable to assume that NMB may also be related to spindle cell lipoma, which typically expresses CD34 and may rarely be positive for S100 protein [ 12 ], like the case herein reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the immunohistochemical coexpression of CD34, actin and calponin in our case would favor the existence of a link between NMB and myofibroblastoma. On the other hand, it is widely accepted that myofibroblastoma and spindle cell lipoma share many features [ 10 ], including genetic aberrations [ 11 ], and it is well known that their morphologic findings may occasionally overlap [ 12 ]. Thus, it seems reasonable to assume that NMB may also be related to spindle cell lipoma, which typically expresses CD34 and may rarely be positive for S100 protein [ 12 ], like the case herein reported.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports about accompany. It was reported that MFB was associated with spindle cell lipoma (SCL) with expression of S-100 in foci [3]. It may be argued because MFB and SCL had similar chromosomal aberrations and there was a genetic link between them [11].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many unusual morphologic variants besides the classical type have been recognized [2]. Few cases of MFB associated with another lesion have been reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus gibt es in der Literatur Hinweise darauf, dass sowohl mammäre wie extramammäre spindelzellige Lipome überlappende histomorphologische Eigenschaften mit Myofibroblastomen aufweisen können [11]. Vereinzelt sind auch Übergangsformen beschrieben [12,13].…”
unclassified